The Effect of Cooperative Learning and Thinking Ability toward Writing Skill of Exposition Paragraph - Etik, Etik; Lustyantie, Ninuk; Emzir, Emzir (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
The purpose of this study is to investigate the effect of Numbered Head Together (NHT) type and Cooperative Script (CS) type of cooperative learning (creative and critical thinking ability) toward the skill of writing exposition paragraph to the second-semester students of Indonesian Language and Literature Education Study Program, University of Cokroaminoto. This study employed the quantitative research approach of the experimental method with a 2x2 factorial design. The test results of the exposition paragraph writing and the thinking ability were analyzed by using a two-way ANOVA design with 0.05 of the significance level. The sample of this study used the multi-stage random sampling technique for 68 students. The result of this research found that students could have high scores in writing exposition paragraphs if teachers employed the cooperative learning model of NHT type so that they could possess the critical thinking ability. The students who had high critical thinking skills got better scores in writing. Conversely, the students who had low critical thinking skills got lower scores in writing.